Stroke knowledge and attitudes influence early hospital arrival in acute ischemic stroke: a multicenter cross-sectional survey from Hubei Province, China - Wu, Xiangbo; Zhou, Qin; Jiang, Xiao; Fan, Fan; Wang, Weijun; Wang, Jinhua; Zhou, Gang; Wan, Feng; Xia, Guangming (Frontiers in Neurology, 2025)
BackgroundPrehospital delay remains a major challenge in China and is a critical barrier to timely intravenous thrombolysis (IVT) in patients with acute ischemic stroke (AIS). However, the contributing factors—particularly the roles of stroke knowledge and attitudes—are not yet fully understood. This study aimed to examine the associations between stroke knowledge, attitudes, and other potential covariates with prehospital delay.MethodsWe conducted a multicenter, cross-sectional study between June and December 2023 across fifteen certified stroke centers affiliated with general hospitals in Hubei Province, China. Data on sociodemographic characteristics, stroke knowledge and attitudes were collected using a structured, self-administered questionnaire. Multiple logistic regression analyses were performed to identify factors associated with prehospital delay.ResultsA total of 1,870 AIS patients were included; 428 (22.9%) arrived within 3 h, and 704 (37.6%) within 6 h of symptom onset. Median prehospital delay was 11.0 h (IQR: 4.0–30.0). Multivariate logistic regression analysis revealed that higher stroke knowledge scores (adjusted OR, 1.15; 95% CI, 1.09–1.21) and higher stroke attitude scores (adjusted OR, 1.26; 95% CI, 1.18–1.33) were significantly associated with earlier arrival. Additional predictors included experiencing stroke onset at a location within 20 km of the hospital (adjusted OR, 2.50; 95% CI, 1.87–3.34), sudden progression of symptoms (adjusted OR, 2.64; 95% CI, 2.05–3.39), NIHSS score ≥6 at admission (adjusted OR, 1.34; 95% CI, 1.02–1.75), and arrival by ambulance (adjusted OR, 1.99; 95% CI, 1.48–2.68). Similar associations were observed for the 6-h threshold.ConclusionOur findings highlight that greater stroke knowledge and positive attitudes significantly influence early hospital arrival in AIS patients. Sudden symptom onset, ambulance use, and shorter transfer distances also facilitate timely hospital arrival, whereas mild stroke contribute to delays. Thus, future stroke interventions should take these characteristics into account, which might ultimately help to promote earlier hospital arrival.